Rancangan Aplikasi Marketplace UMKM D’Camilan Di kota Padang Menggunakan Aplikasi Blogger - Yolanda Irma Julia Putri; Muhammad Rakha; Dhea vega Anandha; Sularno; Rafidola Mareta Riesa (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2024)
The aim of this research is to design a marketplace application for D'Camilan Micro, Small and Medium Enterprises (MSMEs) in Padang City using the Blogger platform. With increasing public interest in local products, the use of digital technology has become important to increase the visibility and accessibility of MSME products. This research uses a design method consisting of needs analysis, appearance design, and implementation of basic features such as product catalogs, ordering systems, and promotional media. The results of this design show that using Blogger as a platform allows MSMEs to utilize existing tools at a lower cost, while still providing a good user experience. It is hoped that this application can increase sales and expand the market reach of D'Camilan MSMEs in Padang City and encourage local economic development.